Epidemiology and molecular study of Leptospira spp. in bats and rodents in the Republic of Guinea ... - Aissatou BOIRO; Taliby Dos CAMARA; Sanaba BOUMBALY; Ekaterina NAYDENOVA; Mamadou Yéro BOIRO (Zenodo, 2023)
Introduction: Leptospirosis is a zooanthroponosis caused by spirochete bacteria called leptospire of the genus Leptospira. Objective: To contribute to the knowledge and circulation of the Leptospira germ in humans in the Republic of Guinea. Methods: This prospective and descriptive cross-sectional study lasted 18 months, from June 2019 to December 2020. Results: 687 samples, including 388 bat kidney tissues and 299 kidney tissues from captured rodents, were analysed at IRBAG's Guineo-Russian laboratory. The molecular diagnostic technique (RT-qPCR) and sequencing were carried out. Among rodents, 15 species were captured in the various administrative regions of Guinea: Mastomys natalensis, Mastomys erythroleucus. Mastomys sp, Praomys daltoni, Praomys rostratus, Praomys sp, Rattus rattus, Mus musculus, Mus musculoides, Mus sp, Lemmiscomys striatus, Gerbilliscus guineae, Cricetomys gambianus, Crocidura olivieri, Crocidura sp. The N’zérékoré region recorded the highest number of captures 226 (87 Mastomys ...